Dynamics of Human Resource Management in Livestock Sector Family Business Development in Malang, East Java - Indira Oktavianti; Landreas Utama Lie; Sopiah Sopiah; Ludi Wishnu Wardana (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to comprehensively explore the dynamics of human resource management (HRM) to develop family businesses in Bantur sub-district, Malang Regency, East Java. Identify the challenges and strategies used in managing human resources in the family business partnership model. This research method uses a qualitative approach by understanding the phenomenon in depth related to the object of research. The results of this study indicate that there is a Human resource management (HRM) in family businesses in the Hong Kong caterpillar cultivation sector in Bantur sub-district, Malang district based on trust in employees, with attention to ethics-based conflict management.This research provides a new contribution regarding in-depth exploration of the dynamics of HRM in micro, small, and medium scale enterprises (MSMEs) in the livestock sector, which has not been widely researched, especially in the context of Human Resource Management (HRM). The practice of HRM using a qualitative approach in a family business with a partnership model produces a deep and complex understanding of its relationship with family values, business structure, and resource management on an MSME scale.